Simultaneous Measurement of Serum Testosterone and Dihydrotestosterone by Liquid Chromatography-Tandem Mass Spectrometry - Shiraishi, Steve; Lee, Paul W. N; Leung, Andrew; Goh, Victor H. H; Swerdloff, Ronald S; Wang, Christina (Clinical chemistry (Baltimore, Md.), 2008)
Background: Recent reports have described inherent problems with androgen immunoassays compared with mass spectrometry analyses. Methods: We developed a method for measuring serum testosterone (T) and 5α-dihydrotestosterone (DHT) simultaneously via liquid–liquid extraction followed by liquid chromatography–tandem mass spectrometry (LC-MS/MS) with positive-mode electrospray ionization. Results: The DHT and T calibrators showed a linear response from 0.069 nmol/L to 34.4 nmol/L and 69.3 nmol/L, respectively. T interference in the DHT assay and vice versa were negligible. Within- and between-run imprecision values were <5% for both analytes. Percent recoveries of T and DHT spiked into samples at concentrations spanning the calibration curve were 100%–113% and 98%–107%, respectively. The lower limit of quantification was 0.069 nmol/L for both steroids. Serum T concentrations measured by LC-MS/MS were different from those obtained by RIA, especially at lower T concentrations. Serum DHT concentrations measured by LC-MS/MS were markedly lower than those generated by RIA because of the nonselectivity of the RIA without chromatography. The reference intervals (mean ± 2 SDs) determined for T and DHT were 9.2–33.7 nmol/L and 0.47–2.65 nmol/L, respectively, for 113 healthy adult men and 0.33–2.02 nmol/L and 0.09–0.91 nmol/L, respectively, for 133 healthy premenopausal women. Conclusions: We have developed and validated a selective and precise method for simultaneous measurements of serum T and DHT that can be adopted for routine measurements of these androgens in health and disease in men and women.